Implementasi Implementasi Konseling Individual Dengan Pendekatan Client Centered Dalam Membentuk Kemandirian Anak Berkebutuhan Khusus Di Slb-B Negeri Pembina Palembang - Rista Yuni Aprilina; Amin Sihabuddin; Hartika Utami Fitri (ScidacPlus, 2023)
Independent is standing alone on the capital of confidence in oneself. From this basic capital, a person will have great confidence to be able to do and do something on his own. This research is entitled